2010
DOI: 10.1111/j.1468-246x.2010.001363.x
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the crisis on social security administrations: A review of the findings of an ISSA survey

Abstract: This article reviews the findings of a major survey conducted in 2009 by the International Social Security Association (ISSA) on the impacts of the financial and economic crisis on social security administrations. The findings reveal that a majority of administrations have been negatively affected in terms of diminished investment returns on social security funds and reduced contribution income and are challenged by increased expenditure on benefits. In spite of all this, the findings indicate that administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Defined contribution schemes are generally more vulnerable to market fluctuations, especially in economies like Ghana and Nigeria, where rates of inflation are high and general market conditions are highly unpredictable. The 1970s' economic crises and their impacts on NPFs in English‐speaking sub‐Saharan Africa (Mkulo, 1994), as well as the challenges posed by the 2008 economic crisis for pension systems in general (McCord, 2010; Orton, 2010; Pino and Yermo, 2010), highlight the weaknesses of defined contribution plans and show that such pension systems are not immune to market failures.…”
Section: An Evaluation Of Defined Contribution Plans In the Context Omentioning
confidence: 99%
“…Defined contribution schemes are generally more vulnerable to market fluctuations, especially in economies like Ghana and Nigeria, where rates of inflation are high and general market conditions are highly unpredictable. The 1970s' economic crises and their impacts on NPFs in English‐speaking sub‐Saharan Africa (Mkulo, 1994), as well as the challenges posed by the 2008 economic crisis for pension systems in general (McCord, 2010; Orton, 2010; Pino and Yermo, 2010), highlight the weaknesses of defined contribution plans and show that such pension systems are not immune to market failures.…”
Section: An Evaluation Of Defined Contribution Plans In the Context Omentioning
confidence: 99%
“…On the one hand, it has been suggested that globalization has hit developing countries harder as they are vulnerable to market fluctuations, already at a disadvantage in the western-dominated global market and are still establishing their welfare systems (Hill, 2006: 276–8). On the other hand, it appears that the recent economic crisis has been less severe in the South compared to OECD countries (Orton, 2010). Hence, the impact of globalization and crisis may vary at different developmental levels.…”
Section: Globalization Crisis and Social Policy Development: The Debatementioning
confidence: 99%